(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
In irrigated areas, along with the land, irrigation water also acts as a general means of production. The inseparable unity in the use of land and water determines the specifics of maintaining a land cadastre in irrigated areas of agriculture.